Treping System (New Trebit for Bookkeeping System): Implementasi Triple Entry Accounting dalam Sistem Entitas Pendidikan - Muhammad Fitrah Mahaini; Fadhilah Regina Aurel Danessa; Arum Kusumastuti Wulandari (Pusat P2M Politeknik Negeri Batam, 2022)
ABSTRACT Quality education will be the foundation of the government's efforts to encourage the achievement of sustainable development goals and targets in the 2030 Sustainable Development Goals (SDGs) era. One aspect in the education sector that plays an important role in realizing these goals is the use of an appropriate accounting system. The purpose of this study is to analyze the implementation of the triple entry bookkeeping on the accounting system in educational entities. The implementation is considered to have several positive impacts, including: (1) Providing budget information; (2) Automatically validate transactions; (3) Providing an integrated public ledger; and (4) Increase trust and transparency. This research was used library research. The data obtained were analyzed using descriptive analysis techniques with a deductive mindset. The proper and accurate application of triple entry bookkeeping will fundamentally minimize the fault, reduce internal fraud and improve operational efficiency of educational entities as well as improve operational efficiency of educational entities. ABSTRAK Pendidikan berkualitas akan menjadi tumpuan upaya pemerintah dalam mendorong tercapainya tujuan dan sasaran pembangunan berkelanjutan dalam era Sustainable Development Goals (SDGs) 2030. Salah satu aspek di sektor pendidikan yang berperan penting untuk mewujudkan tujuan tersebut adalah penggunaan sistem akuntansi yang tepat guna. Tujuan dari penelitian ini adalah untuk menganalisis implementasi triple entry bookkeeping terhadap sistem akuntansi dalam entitas pendidikan. Implementasi tersebut dinilai akan menghasilkan beberapa dampak positif antara lain: (1) Menyediakan informasi anggaran; (2) Memvalidasi transaksi secara otomatis; (3) Menyediakan public ledger yang terintegrasi; dan (4) Meningkatkan kepercayaan dan transparansi. Penelitian ini menggunakan metode kepustakaan (library research). Data yang diperoleh dianalisis dengan teknik deskriptif analisis dengan pola pikir deduktif. Penerapan triple entry bookkeeping dengan tepat dan akurat, secara fundamental akan meminimalisir resiko kesalahan, mengurangi penipuan internal dan meningkatkan efisiensi operasional entitas pendidikan serta meningkatkan efisiensi operasional entitas pendidikan.